2022
DOI: 10.3389/fpubh.2021.728117
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Mental Health Outcomes and Changes in Lifestyle Behavior Index Among Saudi Adults 16 Weeks After COVID-19 Pandemic Lockdown Release

Abstract: BackgroundThe current (coronavirus disease 2019 [COVID-19]) pandemic is still uncontrolled with associated dramatic changes in daily lifestyle activities. Evidence for studying the impact of these health behavior changes on our mental health is limited. Therefore, this study aimed to estimate the prevalence of psychological distresses and assess their influence by the change in the composite lifestyle behaviors before the COVID-19 pandemic till 16 weeks after the lockdown release in Saudi Arabia.MethodsThis cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…In Saudi Arabia (KSA), several studies confirm the results found in different countries in the world and indicate that the negative lifestyle behavioral changes caused by confinement were significantly associated with stress and anxiety (Alamri et al, 2020;Boughattas and Tolba, 2021;Abd El-Fatah et al, 2022). The study of show that 58% of the participants suffered from anxiety, depression, and insomnia.…”
Section: Introductionmentioning
confidence: 55%
“…In Saudi Arabia (KSA), several studies confirm the results found in different countries in the world and indicate that the negative lifestyle behavioral changes caused by confinement were significantly associated with stress and anxiety (Alamri et al, 2020;Boughattas and Tolba, 2021;Abd El-Fatah et al, 2022). The study of show that 58% of the participants suffered from anxiety, depression, and insomnia.…”
Section: Introductionmentioning
confidence: 55%
“…In the title and abstract screening stage, 162 records were excluded as irrelevant. After a full-text review of 47 reports, we included 19 studies [ 24 , 31 48 ], all published in English.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Five lifestyle behaviors (physical activity, sleep, sitting, smoking, Body Mass Index (BMI) in kg/m 2 , and dietary habits) were assessed based on reported risk category calculation protocols ( 47 ). Dietary habits were measured based on index values reported by the Saudi Food-based Dietary Guidelines for 14 food items ( 48 ).…”
Section: Methodsmentioning
confidence: 99%